(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of depression and anxiety in patients with melisma. Study Design: A cross-sectional study Place and Duration of Study: This study was conducted at the Department of Dermatology, Farooq Hospital Islamabad in the duration from October, 2022 to July, 2023. Methods: 160 patients presenting with clinically diagnosed melasma since two weeks of either gender having age between 18 to 60 years. We determined the frequencies for anxiety and depression in patients of melasma. Results: The mean age of the patients presenting with acne vulgaris was 33.41±15.40 years. The frequency of anxiety in our study was 54 (33.3%). The frequency of depression in our study was 30 (18.8%). Conclusion: From our study we conclude that the frequency of depression was 54 (33.3%) and anxiety 106 30 (18.8%). in patients with melasma.